Pendampingan Keluarga Perspektif Teori Ketahanan Keluarga Froma Walsh : (Studi Pada Keluarga Dampingan Lazis Sabilillah Kota Malang) - Naqiyyatussa'diyah; Mufidah CH; Muhammad Aunul Hakim (Maqasid: Jurnal Studi Hukum Islam, 2025)
Families who have economically vulnerable conditions sometimes need strengthened resilience because there are various problems that come to them. Lazis Sabilillah Malang city has a program called family assistance with the aim of helping families and underprivileged people who live in Malang City in the form of education, economy, health, and spirituality. Therefore, Walsh's theory regarding the importance of belief systems, organizational patterns, and communication processes is important to study for families facing various challenges in order to maintain family resilience and develop. This research is a type of empirical research with a legal sociology approach. The data source consists of primary data through Lazis Sabilillah assisted family informants and secondary data obtained from books, journals, related legislation. data collection through interviews and documentation. The results showed that the program provided by Lazis Sabilillah was very helpful and effective for the assisted families, besides that the program that had a lot of influence and benefits for the assisted families was spiritual, educational, economic, and finally the health program. Regarding family assistance carried out by Lazis Sabilillah is a reflection of the Walsh family resilience principle. In building meaning during crisis situations, it can mobilize the economy, and strengthen communication in family members. However, most of the assisted family informants have not fulfilled the three Walsh family resilience indicators due to various factors behind them. Keywords: Assisted Families; Family Resilience, Froma Walsh Theory